Chitosan functionalized with heptadentate dinucleating ligand applied to removal of nickel, copper and zinc. (15th March 2021) - Pires, Anderson B.; Vitali, Luciano; Tavares, Amanda; Germano, Carlos A.; Amorim, Suélen M.; Moreira, Regina F.P.M.; Peralta, Rosely A.; Neves, Ademir
Graphical abstract: Highlights: Removal of Cu(II), Ni(II), Zn(II) using derivatized chitosan. Selectivity on the adsorption of metals using derivatized chitosan. The order of the affinity of adsorbent for the metal ions was: Cu(II) > Zn(II)∼Ni(II). Abstract: The preconcentration of metal ions present at low concentration levels in aqueous systems and the selective removal of potentially toxic metals are important applications of adsorption processes. In this study, a heptadentate dinucleating ligand was anchored to chitosan for use in adsorption studies on Zn(II), Cu(II) and Ni(II) ions. The novel adsorbent was characterized by 13 C NMR and FT-IR spectroscopy, TGA and BET surface area analysis. The degree of substitution of the ligand in chitosan, obtained from CHN analysis, was 0.73. The adsorption kinetics followed a pseudo-second-order model. The rate constants and the adsorption capacities for multicomponent systems decreased in the order Cu(II) >> Ni(II) ∼ Zn(II), indicating the preferential adsorption of Cu(II). For Cu(II) ions, the Langmuir model provided the best fitting to the experimental data, and the monolayer Cu(II) adsorption capacity was 0.404 mmol g −1, while the linear isotherm described Zn(II) and Ni(II) ion adsorption.